2021
DOI: 10.1177/10711007211060047
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Survivorship of the INBONE II Total Ankle Arthroplasty

Abstract: Background: The use of total ankle arthroplasty (TAA) in the treatment of ankle arthritis has grown substantially as advancements are made in design and surgical technique. Among the criteria guiding the choice between arthroplasty and arthrodesis, the long-term survival and postoperative outcomes are of crucial importance. Although outcomes of the INBONE I have been published, there is limited midterm survival data for the INBONE II. The purpose of this study was to determine the radiographic and patient-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 60 publications
(99 reference statements)
1
17
0
Order By: Relevance
“…While several case studies and reports have demonstrated complex and successful surgical correction of the fibula and tibia, there is lack of documentation supporting the use of ankle arthroplasty in deformity-driven ankle arthritis secondary to fibular deficiency (3)(4)(5)(6). With the increasing technology and biomechanical advancements in ankle joint arthroplasty in the last 20 years, modular stemmed implants have demonstrated exceptional longevity and success (7,8). In this report we present a case of Type IA fibular hypoplasia treated with total ankle replacement arthroplasty and successful results recorded with over 12 years of follow-up after implantation.…”
Section: Introductionmentioning
confidence: 88%
“…While several case studies and reports have demonstrated complex and successful surgical correction of the fibula and tibia, there is lack of documentation supporting the use of ankle arthroplasty in deformity-driven ankle arthritis secondary to fibular deficiency (3)(4)(5)(6). With the increasing technology and biomechanical advancements in ankle joint arthroplasty in the last 20 years, modular stemmed implants have demonstrated exceptional longevity and success (7,8). In this report we present a case of Type IA fibular hypoplasia treated with total ankle replacement arthroplasty and successful results recorded with over 12 years of follow-up after implantation.…”
Section: Introductionmentioning
confidence: 88%
“…Patients who underwent primary INBONE II or Salto Talaris TAA were found through an institutional review board (IRB) approved registry database search as described by Day et al 4 and Gagne et al 6 The same cohorts from these outcome studies were used for analysis in the present report. After applying exclusion criteria from these studies, the final INBONE II and Salto Talaris patient cohorts included 44 consecutive cases (40 patients) in the INBONE II group and 85 consecutive cases (82 patients) in the Salto Talaris group.…”
Section: Methodsmentioning
confidence: 99%
“…After applying exclusion criteria from these studies, the final INBONE II and Salto Talaris patient cohorts included 44 consecutive cases (40 patients) in the INBONE II group and 85 consecutive cases (82 patients) in the Salto Talaris group. 4,6 All cases from the INBONE II group were performed by 4 fellowship-trained foot and ankle orthopaedic surgeons. The same 4 surgeons performed TAA in the Salto Talaris group, with the addition of 1 extra surgeon who was not involved in the INBONE II cohort.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations